(3OQGSI ebGQfIs - (3RjGO UHMj(B, (3PjGHs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2011)
(3GdTQcI aj Gdabg GdGSdGej h GdbGfhf (B: (3eaghe GdTQcI h eTQhYjJgG , CbSGegG h GfgGA GdTQcI , eaghe GdGadGS h YdGbJg HGdGYSGQ h GdJUajI , eTQhYjI fXGe GdGadGS h CgejJg h ZGjGJg , GdNUheI h GdGNUGU aj OYhi GadGS GdTQcI h TQhW GadGS GdTQcI , GKQ GdGadGS GdaYdj Ydi GdTQcI h CKQ ETgGQ GadGS GdTQcI YdjgG , BKGQ GadGS GdTQcI Ydi GdOjhf BKGQ ETgGQ EadGS GdTQcI Ydi GdTQcGA h GdeOQGA GdYGejf h CYVGA eLdS GdGOGQI , CKQ EadGS GdTQcI Ydi GdOGFfjf , GfJgGA GadGS GdTQcI h HjY CehGdgG , Mb GdGSJQOGO h JMbjb GdOjhf h bSeI CehGd GdTQcI Ydi GdOGFfjf (B.s
Keywords: (3GdGadGSs; (3GdGadGS `` abg GdGSdGejs; (3GdGadGS `` bGfhf JLGQjs; (3Gdabg GdGSdGejs; (3GdbGfhf GdJLGQjs